Time-dependent laxative effect of sennoside A, the core functional component of rhubarb, is attributed to gut microbiota and aquaporins. (15th July 2023) - Zhang, Mei-Mei; Gong, Zhi-Cheng; Zhao, Qi; Xu, Ding-Qiao; Fu, Rui-Jia; Tang, Yu-Ping; Chen, Yan-Yan
Abstract: Ethnopharmacological relevance : Sennoside A is a natural anthraquinone component mainly derived from rhubarb and has been routinely used as a clinical stimulant laxative. However, long-term application of sennoside A may lead to drug resistance and even adverse reactions, thus limiting its clinical use. Therefore, to reveal the time-dependent laxative effect and potential mechanism of sennoside A is of critical importance. Aim of the study : This study was conducted to investigate the time-dependent laxative effect of sennoside A and unveil its underlying mechanism from the perspective of gut microbiota and aquaporins (AQPs). Materials and methods : Based on a mouse constipation model, 2.6 mg/kg sennoside A was administered orally for 1, 3, 7, 14 and 21 days, respectively. The laxative effect was assessed by the fecal index and fecal water content, the histopathology of the small intestine and colon was evaluated by hematoxylin-eosin staining. Gut microbiota changes was observed by 16S rDNA sequencing, and colonic AQPs expression was analyzed by quantitative real-time polymerase chain reaction and western blotting. Partial least-squares regression (PLSR) was used to screen out the effective indicators contributing to the laxative effect of sennoside A. The effective indicators were then fitted to time by a drug-time curve model to analyze the trend of efficacy of sennoside A, and the optimal time of administration was derived by comprehensive analysis with a three-dimensional (3D) time-effect image. Results : Sennoside A had a significant laxative effect at 7 days of administration with no pathological changes in the small intestine or colon; however, at 14 or 21 days of administration, the laxative effect diminished and slight damage to the colon was observed. Sennoside A affects the structure and function of gut microbes. The alpha diversity showed that the abundance and diversity of gut microorganisms reached the highest value after 7 days of administration. Partial least squares discriminant analysis showed that the composition of the flora was close to normal when administered for less than 7 days, but was closest to the composition of constipation over 7 days. The expression of aquaporin 3 (AQP3) and aquaporin 7 (AQP7) decreased gradually after the administration of sennoside A, with the lowest expression at 7 days, and then increased gradually afterwards, while the expression of aquaporin 1 (AQP1) was the opposite. The PLSR results showed that AQP1, AQP3, Lactobacillus, Romboutsia, Akkermansia and UCG_005 contributed more to the laxative effect of the fecal index, and after fitting with the drug-time curve model, each index showed a trend of increasing and then decreasing. The comprehensive evaluation of the 3D time-effect image concluded that the laxative effect of sennoside A reached its best after 7 days of administration. Conclusion : Sennoside A should be used in regular dosages for less than one week, as it provides significant relief of constipation and exhibits no colonic damage within 7 days of administration. In addition, Sennoside A exerts its laxative effect by regulating gut microbiota of Lactobacillus Romboutsia, Akkermansia and UCG_005 and water channels of AQP1 and AQP3. Graphical abstract: Image 1 Highlights: For constipation relief, Sennoside A should be used at regular dose for less than 7 days. Sennoside A exerts the laxative effect by regulating gut microbiota and aquaporins. The optimal time is obtained through a comprehensive analysis of fecal index, intestinal histopathology, gut microbiota and aquaporins.